Packet communications on a mobile radio channel - Karim, M.R. (1986)
This report has explored the possibility of transmitting packetized data over a Rayleigh fading channel. The random errors due to the FM channel impairments have been ignored, and only burst errors that characterize the fading channel are considered. The protocol simulated is the widely used HDLC protocol which requires a frame to be retransmitted only when the remote end has detected errors in the received frame. Packets are sufficiently short so that most of them fall in the interfade time intervals. This leads to a high transmission efficiency. It is shown that the delay and throughput depend on the fade statistics. Also, for a given vehicle speed, they both improve monotonically as the packet size decreases. However, a smaller packet size increases the overhead fraction of the packet and thus reduces the effective throughput. Furthermore, there is a range of values of the packet size over which the delay is small and the efficiency high.